U-PB DATING OF THE VERKNIY UFALEY INTRUSION, MIDDLE URALS, RUSSIA: A MINIMUM AGE FOR SUBDUCTION AND AMPHIBOLITE FACIES OVERPRINT OF THE EAST EUROPEAN CONTINENTAL MARGIN - Hetzel R.; Romer R. (My University, 1999)
The Palaeozoic Uralian orogen formed by accretion of island arcs and microcontinents along the eastern margin of the East European platform. In the middle Urals, a promontory of the East European platform, the Ufaley Complex experienced eclogite facies conditions followed by an amphibolite facies overprint. The Verkniy Ufaley intrusion crosscuts the amphibolite facies foliation in the East Ufaley Complex and thus postdates the two metamorphic events. A concordant U–Pb age of 316±1 Ma obtained on magmatic titanite dates the intrusion of the pluton and provides a minimum age for subduction and subsequent amphibolite facies metamorphism of the East European continental margin. Zircon yields discordant age data that reflect the involvement of Proterozoic crustal sources.
Keywords: Proterozoic; Palaeozoic; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic; Палеозой